Utilization of fruit and vegetable waste to produce value-added products: Conventional utilization and emerging opportunities-A review. (January 2022) - Ganesh, K. Selva; Sridhar, Adithya; Vishali, S.
Abstract: Fruit and vegetables are one of the most consumed commodities globally, accounting for more than 42% of total food wastage. These vegetal foods can be consumed raw, processed, or taken as an addition to other food items. The continuous rise in population, in addition to technological advancements, has led to an imbalance in demand supply, resulting in increased food wastage globally. Although source reduction and recycling have shown promising results, more evaluations concerning economics and environmental impacts need to be given importance. The need of the hour lies in finding a possible method towards effective utilization for fruit and vegetable waste to generate value-added products which are more eco-friendly, cheaper, and sustainable. Thus, this article attempts to focus on the conventional and emerging opportunities of fruit and vegetable waste to generate value-added products. Conventional utilization, namely briquetting, waste to energy conversion, enzymatic degradation, and adsorption, as well as emerging opportunities in the areas of nutraceuticals, packaging, flavoring agents, and waste induced nanoparticles, have been emphasized. Additionally, recommendations and future perspectives towards better utilization of vegetal waste have been given importance. This review aims to narrow down the path towards evaluating the most techno-economic and efficient waste management technique for fruits and vegetable valorization, which can be promoted in the long term. Graphical abstract: Image 1 Highlights: Emerging opportunities towards valorization of fruit and vegetable waste to generate value added products are emphasized. Fruit and vegetable waste as adsorbents in addition to their usage in nutraceutical industry are discussed. Perspectives and recommendations for developing a sustainable system are highlighted. A more concerted approach in managing waste considering aspects of cost and sustainability is focused.